A power investigation of Alexander Govern test with adaptive trimmed mean as a central tendency measure - Abdullah, Suhaida; Syed Yahaya, Sharipah Soaad; Othman, Abdul Rahman (2013)
This study investigated on power of the test for Alexander Govern method using adaptive trimmed mean as a central measurement (AH).The power of the test is controlled by three parametric specification namely significance level (α), sample size (n) and effect size (EF).Previous studies on Type I error rates found that this method is robust and perform very well even under extreme conditions.To check on the strength and weakness of the method with regards to power of test, variables such as the shape of the distribution of data, variance ratio, sample sizes and the pair between sample sizes and unequal variance were manipulated to create various conditions.Results from this study show that the power of the AH test can be considered high in all of the normal distribution.High power test is also consistent under non normal data for the case of unbalanced sample sizes and equal variance of positive pairing.